OPTIMASI WAKTU PEMANASAN DALAM ANALISIS ASPARTAM SECARA SPEKTROFOTOMETRI VISIBEL DAN PENERAPANNYA UNTUK PRODUK MINUMAN SERBUK BERKARBONASI - , NURBAYANTI FADILLAH, Prof. Dr. Endang Tri Wahyuni, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In this research, optimization of heating time on the aspartame analysis using ninhydrin reagent by means of Visible Spectrophotometry has been done. This method was applied to determine aspartame content in carbonated beverage powder product. The analysis was based on the reaction between aspartame with ninhydrin at pH 5, then heated and rested for 5.5 hours. The absorbance of resulting solution was measured at Î» 570 nm. The result of this research showed that optimum heating time is 5 minutes. Calibration curve was linear in concentration range of 0- 0.019 M with regression equation y = 20.42x â 0.005 with a regression coefficient of 0.994 and limit of detection (LOD) and limit of quantification (LOQ) of 2.297Ã10-3 M and 0.008 M, respectively. Statistically, it could be stated that analytical method of aspartame could be applied to determine aspartame content in carbonated beverage powder sample and showed that the sample positively contained aspartame of 546 mg/g sample. Key words: Aspartame, ninhydrin, heating time, spectrophotometer.